3x+25=12x-83

Simple and best practice solution for 3x+25=12x-83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+25=12x-83 equation:


Simplifying
3x + 25 = 12x + -83

Reorder the terms:
25 + 3x = 12x + -83

Reorder the terms:
25 + 3x = -83 + 12x

Solving
25 + 3x = -83 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
25 + 3x + -12x = -83 + 12x + -12x

Combine like terms: 3x + -12x = -9x
25 + -9x = -83 + 12x + -12x

Combine like terms: 12x + -12x = 0
25 + -9x = -83 + 0
25 + -9x = -83

Add '-25' to each side of the equation.
25 + -25 + -9x = -83 + -25

Combine like terms: 25 + -25 = 0
0 + -9x = -83 + -25
-9x = -83 + -25

Combine like terms: -83 + -25 = -108
-9x = -108

Divide each side by '-9'.
x = 12

Simplifying
x = 12

See similar equations:

| 3x+30=5x+14 | | 3x^2-4x+5=0 | | 3x-3=11x-43 | | 2x+29=12x-91 | | x^2-6=0 | | 5x-8=6x-1 | | 0=-4x-32 | | 0=28x^2-12x | | 10m+7n=170 | | 7x^2-16x=18 | | x^2-x=25 | | 14x^2*2x+3=0 | | (ax+c)(bx+d)=(bx+c)(ax+d) | | 10d-8=3d-17-2d | | 7x+16-3x=12-6x-6 | | 6x+y=8 | | S=3(r^3)t | | p-5=-12+p | | S=3r^3t | | 2a-5+12c=2a+b | | 5z-12=5z+15 | | (13x-25)+(9x+3)=77 | | -100x=10x^2 | | (0.1x+1)*.1x=2x | | -5(t-1)+9t=7t-6 | | 83=x+59 | | 63-n=15 | | 7+5b=37 | | 42-5=x | | 6+3+c=19 | | (5x-6)+(2x+5)=180 | | 17-x=16-5 |

Equations solver categories